DISEQUILIBRIUM MANTLE MELTING - Bédard J.H. (My University, 1989)
The attainment of equilibrium between basalt and residual peridotite depends on the relative magnitudes of melt segregation rate and solid residue re-equilibration rate. Garnets and pyroxenes (and perhaps spinels) require at least 103 years to equilibrate with melt by volume inter-diffusion. Percolation velocities of melt in porous (1–10%) mantle rocks are of the order of 10−4 to 10−8 cm/s. If the melt moves by homogeneous percolation, then a column of peridotite matrix several kilometers in height must interact with the melt for an equilibrium partitioning of elements to be achieved. If melt segregation also involves flow through dykes, as seems likely, then the time available for equilibration is even shorter, and disequilibration melting is to be expected. By varying the time melt and residues remain in contact, variable equilibration will ensue. This can produce crossing REE profiles in basalts derived by identical degrees of melting from identical sources. Basalt-depleted residues from disequilibrium melting have fractionated REE profiles. This provides as alternative to “cryptic” metasomatism for the enigmatic decoupling of major and trace elements that is observed in many mantle peridotite nodules.